Karakteristik Aliran Fluida di Dalam Asymmetric Diffuser dengan Penambahan Vortex Generator - Klistafani, Yiyin (Politeknik Negeri Ujung Pandang, 2018)
A numerical investigation of asymmetric diffuser which equipped with vortex generator is presented. The investigation is aimed to know fluid flow characteristic in asymmetric diffuser which equipped with vortex generator on the up side of its diverging wall and to determine the effectiveness of using vortex generator on diffuser performance. Numerical investigation method was done by using Computational Fluid Dynamics (CFD) method with Fluent 6.3.26 software and with software of GAMBIT 2.4.6 to designed geometry and discriminated (meshing) it. The procedures performed on numerical investigation were pre-processing, solving, and post-processing stages. The results show that the flow of fluid simulated shear stress transport (SST) k-Ï‰ did not suffer a deflection toward the straight wall shortly at the time when entering the diffuser. Standard k-Îµ predicted the flow was deflected when entering the diffuser. Addition of vortex generator was not able to reduce the amount of adverse pressure gradient effect that occurred within the diffuser so using vortex generator was not effective to improve diffuser performance.